The effect of Air Gap Width on the Focal Properties of Objective Snorkel Lens - Al_Salih, Rafe; Kareem kalil, Nawras (Tikrit Journal of Pure Science, 2024)
The current research dealt with studying the effect of air gap width on the objective properties of the magnetic Snorkel lens used in the scanning electron microscope. The structure of the lens was designed and its properties were studied, and the axial magnetic flux density distribution was calculated (Bz) using the electron optical design program (EOD), The results indicated that the maximum value of the magnetic flux density (Bmax) increased with a decrease in the width of the air gap (S), accompanied by a decrease in the half-width, spherical and chromatic aberrations, and an increase in the resolution of the analysis.